Análise descritiva da cerâmica arqueológica de Itaituba, Pará: primeiros dados para um estudo arqueológico - Malato, Roberto Coutinho (Museu Paraense Emílio Goeldi, 2022)
The discovery of archaeological sites near the municipality of Itaituba, in the middle course of the Tapajós River, has confirmed the archaeological and ethnographic diversity and complexity of the homogeneous micro-region of Tapajós. This work aims to contribute, through ethnoarchaeological studies, to the determination and characterization of the cultures that occupied this region; for this purpose 1210 ceramic fragments from Sítio do Laranjal (PA-IT-23), in Itaituba, were analyzed using the Meggers & Evans 1970 quantitative analysis method for ceramics. The analysis of the ceramics recorded the presence of Cauixi and five other types of antiplastic and the making of the vessels through chordellation with irregular firing and flat bases, as well as the identification of motifs and decorative techniques such as incised lines, dots and scrolls mainly on the lips and edges of the fragments. The mid Rio Tapajós has been described by travelers since the seventeenth century as densely populated by various indigenous groups such as the Mundurukú and Apiaká, but later suffered a great retraction with the arrival of colonizers; the analysis of ceramics, as one of several methods of data analysis, and the application of interdisciplinary research are necessary for the reconstruction and identification of this settlement in a territory practically unexplored by archaeology.